A Study of the Alternative Policies in the Control of a National Economy via Dynamic Programming. - Ho, D. C. C.; Noton, Maxwell (Economica)
This paper attempts to cast a light on some of the long-standing issues regarding the effectiveness and relative merits of alternative policies by simulation studies using an illustrative economic model. No econometric technique has been used to estimate model parameters. It is believed, however, that an empirical model may not be appropriate for studying the potential impact of certain policy variables since we have no guarantee that the econometrically estimated parameters will yield valid dynamic, closed-loop simulations. What is needed therefore is a new estimation technique that uses as its criterion of goodness-of-fit, "How well does the model simulate and predict?" rather than "How well does it fit historical data?".